Biologic Therapy and Surgery for Crohn Disease - Paulson, E. Carter (Clinics in Colon and Rectal Surgery, 2013)
In 1998, infliximab, an antitumor necrosis factor alpha (anti-TNF-α) antibody, was approved for use in the treatment of Crohn disease (CD). Since then, other biologic therapies, including adalimumab and certolizumab pegol (newer anti-TNF-α antibodies), and natalizumab, an antibody against alpha-4 integrin, have also been approved. Here, we review the published studies that examine the relationship between pre- and postoperative biologic therapy and postoperative complications in patients with CD. This body of literature is composed of numerous small, retrospective, heterogeneous studies that demonstrate conflicting and varied results. Overall, the receipt of biologic therapy in the pre- or postoperative period does not appear to significantly increase the risk of postoperative complications. It is, however, difficult to draw any firm conclusions based on the existing level of data. In the future, larger prospective studies are needed to better elucidate the true risks, if any, that the use of biologic therapy poses to patients with CD requiring operation.
Keywords: Crohn disease; surgery; biologic therapy; postoperative complications